HEPATOTOXICITY EFFECTS OF PARACETAMOL-DENIK CLEANSER® CO-ADMINISTRATION - Obasi, Cecilia Nwadiuto; Maagbo, Leyiga Justice; Amaka, Mgbahurike Augustina (Universal Journal of Pharmaceutical Research, 2023)
Aim and Objective: The concurrent use of herbal products with orthodox medicine is on the rise with the risk of herb-drug interaction that could be beneficial or harmful to the body. Paracetamol (acetaminophen) is an anti-pyretic and analgesic drug metabolized by CYP2E1 to give the major hepatotoxin, N-acetyl-p-benzoquinone imine (NAPQI). Denik cleanserâ is an oral herbal preparation from plants part of Occimum grattissimum, Colocynthis citrullus, Khaya ivorensi. The aim of this study was to evaluate the hepatotoxic effects triggered by Denikâ and paracetamol co-administration in rats. The study sought to mimic conventional usage of Denik cleanserâ followed by ingestion of paracetamol, a likely scenario given the popularity of both compounds. Method: Twenty animals were randomly assigned to four groups, the first group (control) received 0.3 mL distilled water, 2nd group received paracetamol 100 mg/kg, 3rd group received Denik cleanserâ2 mL/kg while the 4th group received both paracetamol and Denik cleanserâ at 100 mg/kg and 2 mL/kg daily for 3 days after which biochemical and histological analysis were carried out. Results: From histological analysis revealed that rats that received Denikâ-only and Denikâ/paracetamol (concomitantly) showed markedly distorted liver architecture compared to control indicating toxicity. Similarly, the biochemical analysis results showed a significant (p<0.05) increase in AST and ALT for the Denikâ/paracetamol group compared to the control group indicating a hepatotoxic event. A non-significant increase in ALP and GGT were also observed in the Denik cleanserâ + paracetamol group. Enhanced metabolism of paracetamol by Denik cleanserâ to NAPQI (hepatotoxic metabolite) is indicated as possible mechanism. Conclusion: The results of this study demonstrated the in vivo potential for a herb/drug interaction involving paracetamol and Denik cleanserâ resulting in liver injury.Therefore, caution is strongly advised against its casual, non-medically supervised usage. Peer Review History: Received: 5 October 2022; Revised: 9 November; Accepted: 17 December 2022, Available online: 15 January 2023 Academic Editor: Dr. Nuray Arı , Ankara University, Turkiye, ari@ankara.edu.tr Reviewers: Dr. Sangeetha Arullappan, Universiti Tunku Abdul Rahman, Malaysia, sangeetha@utar.edu.my Prof. Hüsniye Kayalar, Ege University, Turkey, husniyekayalar@gmail.com